Religijność uczonych w perspektywie kognitywnej - Sztajer, Sławomir (Przegla̜d religioznawczy, 2021)
The religiosity of scholars substantially differs from the patterns of religiosity observed in the general population. Scholars are, on average, less religious than nonscholars. Scholars who profess religious faith tend to separate themselves from their religious communities. They also criticize and question the religious truths and keep their faith for themselves, especially in the academic community. Although many scholars perceive the conflict between science and religion, they have the resources to deal with the conflict. This article attempts to explain the specificity of scholars’ religiosity in terms of cognitive mechanisms that make it possible to reconcile religion and science irrespective of whether they are logically coherent or not.